TETAP PODUKTIF DI MASA COVID 19 DESA TANAH BAWAH KECAMATAN PUDING BESAR KABUPATEN BANGKA (OPTIMALISASI POTENSI LOKAL) - Andi Gustomi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2021)
The Covid 19 pandemic has limited people's activities, especially activities outside the home with a large number of people. UBB student community service in Tanah Bawah Village is carried out to provide education so that people can continue to be productive even in the conditions of the Covid 19 pandemic. This community service program is carried out persuasively with online and offline methods. The work programs produced include education about covid-19 in the form of public service videos, distribution of hand sanitizers and masks to residents of Tanah Bawah Village. Education on the application of household-scale catfish cultivation technology, healthy environment education including mutual cooperation and distribution of fruit seeds and organic fertilizers to the community. Education on the clarity of information related to Upang River tourism through the application of signposts to Upang River tourism and socialization of the preservation of Upang River resources and the dangers of using poison / tubing to catch fish. The results of the service through the real work lecture activities showed a very good response from the community and village officials. Village officials also recommended that the KKN time be extended so that student interaction with residents could be longer.